2004
DOI: 10.1038/sj.emboj.7600470
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oncogenic transformation by mammalian Lin-9, a pRB-associated protein

Abstract: Genetic studies in Caenorhabditis elegans identified lin-9 to function together with the retinoblastoma homologue lin-35 in vulva differentiation. We have now identified a human homologue of Lin-9 (hLin-9) and provide evidence about its function in the mammalian pRB pathway. hLin-9 binds to pRB and cooperates with pRB in flat cell formation in Saos-2 cells. In addition, hLin-9 synergized with pRB and Cbfal to transactivate an osteoblast-specific reporter gene. In contrast, hLin-9 was not involved in pRB-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 37 publications
(84 reference statements)
4
71
3
Order By: Relevance
“…We should point out that to our surprise, we have not been able to detect an association between Mip/LIN-9 and pRB as previously reported by Gagrica et al (2004), although identical cell lines (that is HeLa cells) and a variety of anti-pRB antibodies were used. This is illustrated in Figure 1f, in which the anti-Mip/LIN-9 mAbdoes not co-precipitate pRB, although this pocket protein is easily detected in immunoprecipitates with the anti-pRB antibody or by an antibody directed against a known partner of pRB such as E2F3 (lanes 4 and 5).…”
Section: Resultsmentioning
confidence: 47%
See 3 more Smart Citations
“…We should point out that to our surprise, we have not been able to detect an association between Mip/LIN-9 and pRB as previously reported by Gagrica et al (2004), although identical cell lines (that is HeLa cells) and a variety of anti-pRB antibodies were used. This is illustrated in Figure 1f, in which the anti-Mip/LIN-9 mAbdoes not co-precipitate pRB, although this pocket protein is easily detected in immunoprecipitates with the anti-pRB antibody or by an antibody directed against a known partner of pRB such as E2F3 (lanes 4 and 5).…”
Section: Resultsmentioning
confidence: 47%
“…Mip/LIN-9 interacts with mammalian homologs of the Drosophila dREAM complex: B-Myb, p107, p130 and E2F4 Previous reports indicated that in mammalian cells, Mip/LIN-9 interacts with B-Myb (Osterloh et al, 2007;Pilkinton et al, 2007) and it is pulled down with the pocket proteins (Gagrica et al, 2004;Korenjak et al, 2004;Osterloh et al, 2007). Yet, the existence of a dREAM complex and its possible role in cell cycle regulation in mammalian cells has not been addressed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early-passage (p2) Lin9 fl/f CreER T2 MEFs were infected with retroviral expression constructs encoding SV40 LT, LT K1 or LTD434-44 as described (Cotsiki et al, 2004;Gagrica et al, 2004). Cells were selected with 400 mg/ml neomycin for 5 days.…”
Section: Expression Of Sv40 Lt Antigenmentioning
confidence: 99%